β-Arrestin 2 Promotes Hepatocyte Apoptosis by Inhibiting Akt Pathway in Alcoholic Liver Disease - Ying-Yin Sun; Yu-Xin Zhao; Xiao-Feng Li; Cheng Huang; Xiao-Ming Meng; Jun Li (Frontiers Media S.A., 2018)
Alcoholic liver disease (ALD) is a complex process that includes a wide range of hepatic lesions, from steatosis to cirrhosis, and even hepatocellular carcinoma (HCC). Accumulating evidence shows that the cytotoxic effects of ethanol metabolism lead to cell apoptosis and necrosis in ALD. Recently, several studies revealed that multifunctional protein β-arrestin 2 (Arrb2) modulated cell apoptosis in liver fibrosis and HCC, but its role in ALD has not been fully understood. The aim of this study is to explore the function and underlying mechanism of Arrb2 in hepatocyte survival and apoptosis in ALD. In our study, the primary hepatocytes were isolated from the livers of C57BL/6 mice fed EtOH-containing diet, it showed an increased level of Arrb2. EtOH also significantly up-regulated Arrb2 production in AML-12 cells in vitro. Furthermore, TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling) and FCM results demonstrated that knockdown of Arrb2 could inhibit hepatocyte apoptosis induced by EtOH in vivo and vitro while over-expression of Arrb2 induced apoptosis in ALD. In addition, western blot results revealed that Arrb2 remarkably suppressed the Akt signaling. Taken together, our data suggested that Arrb2 may serve as a potential therapeutic target for ALD by promoting hepatocyte apoptosis via Akt suppression.